Momentos de instalação dos implantes - Fernanda Pimenta Piassi (2011)
The demand for treatment of teeth that need to be removed let us to choose the best time to implant placement. Advantages over the maintenance of hard and soft tissues are associated with the placement of these early implants, compared to conventional technique. The placement of implants can be classified into Type 1 (ImmediatePlacement), Type 2 (Placement after initial healing of soft tissues), Type 3(Placement after healing of soft tissue and hard tissue healing initial) and Type 4 (Placement Delayed, after complete filling of the ridge). The purpose of the study is to evaluate the best time for implant placement, considering the important factors of each phase. A literature review was performed and factors such as survival rates, advantages and disadvantages, indications and contraindications, and aestheticfactors were evaluated. The results showed that the prevention of bone remodeling is not possible with implant placement of Type 1 and Type 2, but an advantage may be observed in relation to soft tissues, with the maintenance of gingival architecture. The reason for tooth extraction is a factor that should be considered when this reason is related to chronic periodontitis. Presence of defects in the ridge after tooth extractioncan lead to aesthetic problems important when deciding for placement of Type 1 and Type 2, and should consider installing the later periods. Aesthetic factors as Biotype and Periodontal Maintenance Papillae are important and should be evaluated before the timing of implant placement. In conclusion, there is no superiority of one technique over another and choose the best time of implantation should be done ineach case.